Genetic diversity and relationship of indigenous Kenyan camel breeds: Preliminary results - Mburu, D.N.; Ochieng, J.W.; Han Jianlin; Kaufmann, B.; Kuria, S.G.; Rege, J.E.O.; Hanotte, Olivier H. (APSK, 2002)
Camels are important resource for the desert-dwelling communities. They are a source of income, milk and meat and often play an important sociocultural role in pastoralist societies. In order to help formulate a rational conservation, utilisation and Development policy for the species in Kenya, a diversity of Kenyan camel breeds is being studied using microsatellite markers. Preliminary results on the analyses of four breeds (Rendille, Gabra, Turkana and Somali) with 10 micro\92satellite loci are Reported here. Their relationships with dromedary and bactrian populations from the Arabian Peninsula and the Asian continent have been investigated. Genetic distances between Kenyan camel populations are low with the Rendille and Gabra camels being the most closely related breeds. Kenyan camels are genetically clearly distinct from the Asian and Arabian dromedary as well as from the bactrian camel. They are genetically less variable than non-Kenyan populations, possibly due to a lower number of initial individuals.